Entrepreneurial strategic thinking in the context of uncertain decision-making environments : a cognitive perspective of opportunity recognition - Ramluckan, Sandheep (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.